Determinates of mental illness severity - Alan Griffiths, Christopher (International Journal of Psychosocial Rehabilitation, 2017)
The severity of mental illness has implications for the person experiencing the mental illness, their family and friends, clinicians working with them, service providers, and wider society. However, there is no definition or measure which considers all of the factors associated with mental illness severity. A holistic view of severity is required to understand the full impact of a mental illness and enable effective support, care, treatment, and mental health promoting societies and environments.